PENGARUH PEMADATANTANAH GAMBUT TERHADAP SIFAT FISIK PADA DUA LOKASI YANG BERBEDA - Sandi Perdana; Wawan ' (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
This research aims to find out the effect of compaction of peatland on the physical propertiesat the two different locations. The research was conducted in October- December 2014 at society’s peatland in LubukOgong, Langgam, Pelalawan, Riau. The research used Factorial Split Plot Design (SPD) that consisting 2 factors and 3 replications. Factor I: compaction Level A1, A2, A3, and Factor II: the difference of Location B1 and B2 (Location 1 and Location 2). Parameters were observed those physical characteristics of soil included bulk density, particle density, total pore space, permeability, soil penetration, and water content. The data were analyzed by anova and the means were testedwithLSDsignificant level 5%. The result shows that the increasing of compaction of the peatland produces the increasing of bulk density and the decreasing of total pore space up to the soil deep 15-20 cm. Whereas the analysis result of the water content and particle density shows nonsignificant. The increasing of compaction is also reducing the permeability rate and increasing the value of soil penetration. Keywords: Compaction, Peatland, Physical Characteristics.